2010
DOI: 10.2298/jas1001017a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mycorrhizal fungi on phytoremediating potential and yield of sunflower in Cd and Pb polluted soils

Abstract: The influence of mycorrhizal fungi in uptake of heavy metals, pollution response index and yield of sunflower in degraded soils were investigated. It was a greenhouse experiment with 2 arbuscular mycorrhizae (Glomus mosseae, Glomus intraradices) and a non-inoculation that served as control. The treatments were replicated 3 times in a completely randomized design. Each of the treatment consisted of 30 pots and each pot was filled with 5 kg by weight of dried top soil. Solutions of lead acetate and cadmium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
(12 reference statements)
0
9
0
1
Order By: Relevance
“…Previous studies of Shaheen et al (2007), andEl-Shaikh andMohammed (2009) showed an increase in agronomic growth performance and yield of okra when bio-inoculants were applied to soil. The roots of plant that developed well and had enhanced access to soil nutrients when soils are treated with arbuscular mycorrhiza (Adewole et al, 2010) could be attributable to increased okra yield.…”
Section: Yield Of Okramentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of Shaheen et al (2007), andEl-Shaikh andMohammed (2009) showed an increase in agronomic growth performance and yield of okra when bio-inoculants were applied to soil. The roots of plant that developed well and had enhanced access to soil nutrients when soils are treated with arbuscular mycorrhiza (Adewole et al, 2010) could be attributable to increased okra yield.…”
Section: Yield Of Okramentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) can be integrated into soil management to achieve low-cost sustainable agricultural systems (Hooker and Black, 1995). AMF improve plant-water relations and thus increase the drought resistance of host plants (Nelsen, 1987), improve disease control (Khan, 2006) and increase mineral uptake and yield of crop (Adewole et al, 2010), hence, reduce the use of fertilizers. Mycorrhiza is undoubtedly of extraordinary importance in plant production, plant and soil ecology and plays a key role in sustainable agriculture (Bethlenfalvay et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of contaminants can also occur through fungal structures such as arbuscules, vesicles and vacuoles, minimizing toxicity in the plant itself [191]. Finally, since AMF leads to enhanced plant nutrition and water availability resulting in an increase in plant yield, AMF may indirectly dilute the effects of heavy metals by promoting plant growth [208,215].…”
Section: Remediation Of Heavy-metal Contaminated Soilsmentioning
confidence: 99%
“…A recent review found that AMF could be used as a biomanagement tool in order to reduce phosphate fertilizer application by up to 80% [95,96]. Yield has been known to increase when there is a plant-AMF association in stressed environments, such as nutrient deficiency [95], salinity stress [123] and heavy metal pollution [215]. The successful use of plants in soil restoration depends on mycorrhizal associations [200], and it has been demonstrated that a 'phytomicrobial' approach to soil restoration is an economically viable option [96].…”
Section: Management Implicationsmentioning
confidence: 99%
“…Particularly high levels of elements found in synthetic fertilisers like sodium and potassium have been reported to lead to soil and water pollution and loss of biodiversity in soils [1]. One of the most essential macronutrients for plant growth is phosphorous.…”
Section: Introductionmentioning
confidence: 99%